Women's Organizations and Antisemitism: The First Parliamentary Elections in Independent Poland. Issue 4 (28th July 2021) - Stępień, Aneta
Abstract: This article explores the context of the first parliamentary elections in independent Poland in January 1919, focusing on the National Democratic Party's (ND) election campaign addressed to Polish women and how anti-Jewish slogans were used to mobilize the participation of the female electorate. Before the First World War, ND, led by Roman Dmowski, was the most fervent opponent of women's enfranchisement (Gawin 2015); yet, after the introduction of suffrage, and one month before the elections, the party created the National Women's Organization (NOK), affiliated with ND, tasked with running an election campaign aimed at ethnically Polish women. The article demonstrates that ND instrumentalized female voters and their newly obtained right to win the elections and gain advantage over its largest rival, the Polish Socialist Party (PPS, Polska Partia Socjalistyczna). It argues that members of NOK, who used antisemitic, ultra-nationalistic, and Catholic propaganda in the election campaign, became one of the major advocates of the party's ethno-nationalist vision of Poland; consequently, they significantly contributed to the worsening of Polish-Jewish relations in the interwar period. The article also looks at the critique of the extreme nationalism and antisemitism within ND and NOK by individual female activists and groups not affiliated with Dmowski's party.